Physical and chemical properties of bentonite and its influence on acid and alkaline indicators and fertility of sod-podsolic sandy loamy soil (Retisols) - A. V. Kozlov; A. H. Kulikova; I. P. Uromova (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
The article presents data on how bentonite clay (applied at reclamation rates) affects acid-alkaline characteristics and fertility indicators of soil (sod-podsolic sandy loamy soil - retisols). The experiment was conducted in the Nizhny Novgorod region. Physical and chemical properties of the used bentonite clay were preliminary studied. It is characterized by alkaline reaction of aqueous solution (pH 10.9) and of salt extract as well (pH 9.8) and undergoes electrolytic dissociation. The micro-plot field experiment which lasted over 3 years revealed some positive effect of bentonite application. As a result, the lowering of exchangeable soil acidity (by 0.31. pHKci units) and hydrolytic soil acidity (by 0.20 mg-eqv./100 g) was recorded, substantial reduction of aluminium soluble forms content (up to 48 %) was noticed as well, meanwhile the content of exchangeable Ca2+ and Mg2+ increased by 0.70 and 0.24 mg-eqv./100 g correspondingly. Bentonite application contributed to humus preservation in the soil and humus content was maintained at 1.221.28 % level. Moreover, this practice helped to increase the content of soluble (available) phosphorus and potassium compounds (on average by 27-30 % depending on experiment trial). The studied bentonite clay was proved to have stabilizing effect on acid-alkaline and nutrition balances in the soil. Some interaction between mineral soil part and bentonite clay is supposed to take place which results in the reconstruction of chemically-active fine particles (so-called active mineral centers) in soil adsorption complex.